Fiber-optic sensors for biomedical applications - Tosi, Daniele; Perrone, Guido (Professor of Electronics and Telecommunications) (Artech House applied photonics series., 2018)
This authoritative new resource presents fiber optic sensors and their applications in medical device design and biomedical engineering. Readers gain an understanding of which technology to use and adopt, and how to connect technologies with their respective applications. This book explores the innovation of diagnostics and how to use diagnostic tools.n nPrinciples of fiber optic sensing are covered and include details about intensity-based sensors, fiber bragg gratings, distributed sensors, and fabry-perot interferometers. This book explores interrogation software, standards for medical sensors, and discusses protocols and tools for validation. Various medical device engineering and applications are examined, including sensor catheterization, cardiovascular sensors, diagnostic in gastroscopy, urology, neurology, sensing in thermal ablation. Applications and detection of SPR sensors are presented, along with minimally invasive robotic surgery, smart textiles, wearable sensors and fiber-optic spectrometric sensors. This is a one-stop reference on fiber optic sensors for biomed applications.